Umgang Mit Heterogenität Geschlechtsbezogene Zusammenarbeit in Kindertagesstätten. - Cremers, Michael (Studien Zu Differenz, Bildung und Kultur Ser., 2020)
Male employees in daycare centres are still uncommon. Nevertheless, the first significant changes in the gender distribution in daycare facilities have been achieved through political efforts and strategies to attract more men to day care centres. The study uses group discussions with teams in daycare centres to reconstruct the significance of gender in everyday pedagogical work. A field-specific reorganisation of profession and gender is discernible.